Pancasila dalam Pusaran Diskursus Liberalisme versus Komunitarisme - Otto Gusti Madung (Khazanah: Jurnal Studi Islam dan Humaniora, 2016)
Abstract: This paper attempts to show that a democratic order is not built onthe procedural ethics as assumed by liberals, but it is required a substantiveethical foundation. The reason is the democratic system is not contained ofatomistic individuals without social relations. A democratic process always movesin a society characterized by social relations and the various formation pro-cesses of complex communities. Democracy is built on formal yet fragilecollective identity. In the context of Indonesia, Pancasila is an expression of thecollective identity. As a collective identity, Pancasila has no ends and always inthe process of being and find themselves in a new way. At the end of thepaper, two methods; deliberative and agonistic democracy method are pre-sented. These methods are offered by contemporary political philosophy inresolving conflicts of value in the middle of pluralism.